TGF-β Signaling Regulates the Differentiation of Motile Cilia - Janos Tözser; Ryan Earwood; Akiko Kato; Jacob Brown; Koichi Tanaka; Ruth Didier; Timothy L. Megraw; Martin Blum; Yoichi Kato (Cell Reports, 2015)
The cilium is a small cellular organelle with motility- and/or sensory-related functions that plays a crucial role during developmental and homeostatic processes. Although many molecules or signal transduction pathways that control cilia assembly have been reported, the mechanisms of ciliary length control have remained enigmatic. Here, we report that Smad2-dependent transforming growth factor β (TGF-β) signaling impacts the length of motile cilia at the Xenopus left-right (LR) organizer, the gastrocoel roof plate (GRP), as well as at the neural tube and the epidermis. Blocking TGF-β signaling resulted in the absence of the transition zone protein B9D1/MSKR-1 from cilia in multi-ciliated cells (MCCs) of the epidermis. Interestingly, this TGF-β activity is not mediated by Mcidas, Foxj1, and RFX2, the known major regulators of ciliogenesis. These data indicate that TGF-β signaling is crucial for the function of the transition zone, which in turn may affect the regulation of cilia length.